Prevalence Of African Giant Snails For Parasites In A South-East Region Of CÃ´te d’Ivoire - Mamadou, Karamoko; Saint-Clair, Amani Nâ€™dri; Alassane, TourÃ©; Clarisse, Komoin Oka; Atcho, Otchoumou; Agathe, Fantodji; Philippe, Kouassi Kouassi (European Scientific Journal, ESJ, 2016)
Two species of snails (Achatina achatina and Archachatina ventricosa), from surrounding forest of AzaguiÃ©â€™s district, were collected at the market of the locality aforementioned in order to identify their various parasites. For that, 50 snails of each species were sacrificed. Parasites were searched on the level of the flesh, between the flesh and the shell, the stomach, the intestine, the liver and the reproductive apparatus. The collected parasites were Balantidium spp, the larvae of Protostrongylus spp, the larvae of Dicrocoelium spp and Trichomonas spp. Our results showed that 52% of Achatina achatina and 74% of Archachatina ventricosa were parasitized. Among the parasites collected in the snail Achatina achatina, 95.8% were nematodes and 4.1% were trematodes. Whereas in the snail Archachatina ventricosa, 97.7% were protozoa, 8.8% nematodes and 0.4% consisting with trematodes. The prevalence of Protostrongylus spp (48%) were higher than that of Dicrocoelium spp (4%) in Achatina achatina. For the snail Archachatina ventricosa, the prevalence of parasite were dominated by Trichomonas spp (38%) and Protostrongylus spp (24%).